2020
DOI: 10.1108/xjm-06-2020-0013
|View full text |Cite
|
Sign up to set email alerts
|

Leadership at Godrej: a treasured heirloom transformed into a valuable brand

Abstract: Purpose The purpose of this study is to bring out the success of the Godrej Group, focusing on their leadership styles and discussing how authentic and ethical leadership leads to value-based leadership (VBL), which has its eminence in the post-COVID-19 world. Design/methodology/approach The case study has been designed based on secondary published sources and few informal interactions with the leaders associated with the Godrej Group. Findings It was found that VBL is derived from authentic and ethical le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Second, TL and JS also have a positive relationship, and confirm the findings [20] and [21]. Third, JS has no relationship with OCB, and cannot mediate the relationship between TL and OCB, so it is not by research [28]; and [29].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Second, TL and JS also have a positive relationship, and confirm the findings [20] and [21]. Third, JS has no relationship with OCB, and cannot mediate the relationship between TL and OCB, so it is not by research [28]; and [29].…”
Section: Discussionsupporting
confidence: 75%
“…The relationship between TL and JS is proven in studies [19][20][21] On the other hand, several studies have revealed a positive relationship between job satisfaction and OCB [22][23][24][25][26][27]. Meanwhile, TL and OCB's indirect effect through JS is still little investigated [28][29].…”
Section: Introductionmentioning
confidence: 99%
“…P-Value using T-test: Assuming there is no true difference between the groups being compared, the p-value associated with a t-test indicates the likelihood of receiving a result that is at least as extreme as the one observed. Pattanayak et al, (2020) studied unofficial conversations with the Godrejites and secondary public materials. The many components and prominence of real, moral, and VBL styles are examined.…”
Section: Methodsmentioning
confidence: 99%
“…However, employee performance itself is a theory, which focuses on industrial/organizational psychology, but is difficult to define or measure due to various aspects of job role behavior assessment [14]. [15], said that if performance is "in the form of task performance, it will consist of explicit job behaviors, including primary job responsibilities defined as part of the job description". This performance necessitates greater cognitive abilities from the employee and is aided by task knowledge (knowledge or technical principles required to ensure job performance and have the ability to multitask).…”
Section: Employee Performancementioning
confidence: 99%